2011
DOI: 10.1186/1472-6874-11-33
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stress and anxiety associated with maternal prenatal diagnosis on feto-maternal attachment

Abstract: BackgroundA couple's decision to undergo an invasive test based on a screening test result is a process associated with anxiety. The aim of this study was to determine whether anxiety and prenatal attachment were affected by undergoing an invasive test compared to women in early pregnancy and after a reassuring anomaly scan.Methods200 women were recruited at booking, 14 women and 20 partners after an invasive test and 81 women following an anomaly scan. A questionnaire was completed using the Beck Anxiety Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 43 publications
4
38
0
10
Order By: Relevance
“…19,20 Allison ve ark.nın çalışmasında, kromozom anomalili bebek doğurma ihtimali olan kadınlarda prenatal test öncesi kaygı düzeyinin anlamlı düzeyde yüksek olduğu belirtilmiştir. 7 Suzumori ve ark., non-invaziv tarama testlerinin ileri yaştaki anne adaylarında kaygı düzeyini yükselttiğini ve kaygı düzeyinin yüksek olduğu çiftlerde tarama testini erteleme eğiliminin olduğunu saptamışlardır. 20 Haskovec ve ark.nın çalışmasında, ileri anne yaşı-nın prenatal tarama testleri sırasındaki kaygı düze-yini artırdığı saptanmıştır.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…19,20 Allison ve ark.nın çalışmasında, kromozom anomalili bebek doğurma ihtimali olan kadınlarda prenatal test öncesi kaygı düzeyinin anlamlı düzeyde yüksek olduğu belirtilmiştir. 7 Suzumori ve ark., non-invaziv tarama testlerinin ileri yaştaki anne adaylarında kaygı düzeyini yükselttiğini ve kaygı düzeyinin yüksek olduğu çiftlerde tarama testini erteleme eğiliminin olduğunu saptamışlardır. 20 Haskovec ve ark.nın çalışmasında, ileri anne yaşı-nın prenatal tarama testleri sırasındaki kaygı düze-yini artırdığı saptanmıştır.…”
Section: Discussionunclassified
“…1,[5][6][7] Prenatal tarama testlerinin rutin olarak yapılmaması gerektiğine inanan görüşler, tarama testlerinin kadınlarda fetüste bir sorun olabileceği olasılığına karşın gereksiz endişe ve stres yaratabileceğini savunmaktadır. Diğer taraftan, karşı görüşe sahip olanlar ise tarama testlerinin kadınlara anomalili bebek doğurmayacağına ilişkin güvence vereceğini ve kadınların daha az stresli bir gebelik geçireceğini belirtmektedirler.…”
Section: Anne Yaşının İkili Tarama Testi öNcesiunclassified
See 1 more Smart Citation
“…Para Consonni et al (2010) e Correia e Linhares (2007), quando a mesma é muito intensa, a possibilidade de complicações obstétricas na gravidez e no puerpério aumentam. Além disso, também pode reduzir o bem-estar materno durante a gravidez e ter um efeito deletério sobre a construção da ligação pais-criança (Allison, Stafford, & Anumba, 2012;Gomes & Piccinini, 2010;Hertling--Schaal, Perrotin, Poncheville, Lansac, & Body, 2001).…”
unclassified
“…Despite receiving counseling, women usually experience a variety of psychological responses such as depression, anxiety and stress, deriving from their fears of procedural complications, pain, or worries over possible adverse outcomes from the final test results. (1,2) The study by Allison et al (3) revealed that women undergoing PND procedures experienced higher levels of stress and anxiety. A study by El Hage et al (4) also proved that women in the amniocentesis group expressed significantly higher level of anxiety and depression than those in the control group.…”
Section: Introductionmentioning
confidence: 99%